Pembunuhan Diluar Proses Pengadilan yang Dilakukan oleh Aparatur Negara (Extra Judicial Kiling) Studi Kasus Kilometer 50 Jalan Tol Cikampek Analisis Yuridis Putusan Pengadilan Jakarta Selatan Nomor 868/ Pid.B/2021/PN.Jkt.Sel tanggal 18 Maret 2022 - Apriyadi; Myharto, Wiend Sakty (PT Elaborium Elevasi Indonesia, 2025)
Shootings by state apparatus should be the last resort in accordance with Perkapolri Number 1 of 2009 concerning the Use of Force in Police Actions, taking into account the principles of nesesitas, legality, and proportionality. However, in practice, procedural irregularities often occur that lead to extra-judicial killings. Perkapolri Number 8 of 2009 emphasises that members of the National Police must not commit human rights violations in carrying out their duties. Every individual has the right to legal protection, freedom from torture, punishment and inhumane treatment. Law No. 2 of 2002 authorises state apparatus to act in the public interest, but still within the corridors of the law. The case of the shooting of six members of the FPI Laskar at KM 50 Cikampek Toll Road on 7 December 2020 sparked controversy. The police claimed that this action was an effort to disable threats, but the families of the victims and human rights organisations considered that the action was a form of extrajudicial killing. This case raises questions about the accountability of state apparatus in enforcing the law without committing human rights violations.